Why do countries form regions? The political economy of regional integration - Rasul Shams (Hamburg Institute of International Economics (HWWA), 2002)
To understand the reasons for the formation of regional economic groupings two basic concepts are introduced: association and dissociation. Moreover, the importance of interest groups and strategic groups is discussed, and security and bargaining power as basic political motivations are evaluated. The paper also analyses some political economy arguments regarding the determinants of the size of economic groupings and the dynamics of their development through different stages. Finally it considers regional groupings as strategical coalitions with a deep impact on the future of the world economy. – – Um die Ursachen für die Entstehung regionaler ökonomischer Gruppierungen zu verstehen werden zwei grundlegende Konzepte eingeführt: Absonderung und bedingte Gruppenbindung. Darüber hinaus wird die Bedeutung von Interessengruppen und strategischen Gruppen diskutiert und Sicherheit und Verhandlungsmacht werden als grundlegende politische Motivationen bewertet. Das Papier analysiert ebenfalls einige polit-ökonomische Argumente hinsichtlich der Determinanten für die Größe ökonomischer Gruppierungen und der Dynamik ihrer Entwicklung durch verschiedene Stadien. Schließlich werden regionale Gruppierungen als strategische Koalitionen begriffen, die die Zukunft der Weltwirtschaft stark beeinflussen.
Keywords: F; F15; P16; 330; New Regionalism; Regional Groupings; Interest Groups; Security and Bargaining Power; Strategic Coalitions; Handelsregionalisierung; Wirtschaftsintegration; Public Choice; Gruppentheorie; Koalition; Welt